Social Network, Production Purpose, and Biological Pesticide Application Behavior of Rice Farmers - Li, Zhaoliang; Zhu, Mande; Zuo, Qiaoli (Frontiers in Environmental Science, 2022)
Based on 1202 sampled rice farmers in Hubei Province, China, this paper empirically analyzes the impact of their social network on their biological pesticide application behavior. Furthermore, the internal transmission mechanism of the social network on biological pesticide application behavior of “ration-making” farmers (whose main purpose is to meet the demand for rations) and “profit-making” famers (whose main goal is to maximize their profit) is studied according to different production purposes. The results show that: (1) The social network has a significant positive role in promoting rice farmers' biological pesticide application behavior. (2) Their social network encourages rice farmers to apply biological pesticides by influencing both their behavioral attitude and behavioral efficacy toward green production. (3) The intermediary effect of behavioral efficacy exceeds that of behavioral attitude. (4) Compared with "profit-making" farmers, the biological pesticides application of "ration-making" farmers is stronger affected by their social network. Operation mode, operation scale, and educational level positively affect the pesticide application behavior of “profit-making” farmers, while age imposes a significantly negative influence. Biopesticide application of “ration-making” farmers is negatively affected by age and education level and positively affected by the mode of operation. (5) The behavioral attitude and behavioral efficacy of green production exert significant mediating effects on both types of farmers. Moreover, both intermediary variables exert stronger impacts on "profit-making" farmers. To a certain extent, this study expands the theoretical explanation of the "rational man" in neoclassical economics, and provides reliable evidence, both theoretical and empirical, for effective measures to stimulate green production in rice farmers.